Exocytosis and Endocytosis in Neuroendocrine Cells: Inseparable Membranes! - Houy, Sébastien; Croisé, Pauline; Gubar, Olga; Chasserot-Golaz, Sylvette; Tryoen-Tóth, Petra; Bailly, Yannick; Ory, Stéphane; Bader, Marie-France; Gasman, Stephane (Frontiers in Endocrinology, 2013)
Although much has been learned concerning the mechanisms of secretory vesicle formation and fusion at donor and acceptor membrane compartments, relatively little attention has been paid towards understanding how cells maintain a homeostatic membrane balance through vesicular trafficking. In neurons and neuroendocrine cells, release of neurotransmitters, neuropeptides and hormones occurs through calcium-regulated exocytosis at the plasma membrane. To allow recycling of secretory vesicle components and to preserve organelles integrity, cells must initiate and regulate compensatory membrane uptake. This review relates the fate of secretory granule membranes after full fusion exocytosis in neuroendocrine cells. In particular, we focus on the potential role of lipids in preserving and sorting secretory granule membranes after exocytosis and we discuss the potential mechanisms of membrane retrieval.